Bovine semen sexing: Sperm membrane proteomics as candidates for immunological selection of X‐ and Y‐chromosome‐bearing sperm. Issue 5 (26th May 2021) - Quelhas, Joana; Santiago, Joana; Matos, Bárbara; Rocha, António; Lopes, Graça; Fardilha, Margarida
Abstract: The use of sexed semen in dairy and beef farms ensures the production of animals of the desired sex, resulting in a reduction of costs and an improvement of environmental sustainability. Several methods have been developed over the years, but most of them were abandoned due to their limited efficacy. Currently, the only commercially available method for the separation of X‐ and Y‐chromosome‐bearing sperm is fluorescence‐activated cell sorting. However, this technique is expensive and has limited usefulness for the industry, considering that it cannot produce doses of sexed semen with the desired number of sperm for artificial insemination. Immunological methods have emerged as an attractive alternative to flow cytometry and proteomic knowledge of X‐ and Y‐sperm could be useful to the development of a new method. In this review, we identify the main applications of sexed semen, describe the existing methods and highlight future research opportunities in the field. We consider that immunological methods, based on sperm cell's surface proteins differentially expressed between X‐ and Y‐sperm, could be an interesting and promising approach to semen sexing. Abstract : Immunological methods have emerged as an attractive alternative to flow cytometry and proteomic knowledge of X‐ and Y‐sperm could be useful to the development of a new method. In this review we identify the main applications of sexed semen, describe the existing methods and highlight the future research opportunities in the field. We consider that immunological methods, based on sperm cell's surface proteins, deferentially expressed between X‐ and Y‐sperm could be an interesting and promising approach to sex selection.